Characterization of isobutylhydroxyamides with NGF-potentiating activity from Zanthoxylum bungeanum. Issue 2 (15th January 2016) - Tian, Jun-Mian; Wang, Yuan; Xu, Yuan-Zhen; Yu, Zhao-Cheng; Wei, An-Zhi; Zhang, Wei-Ming; Gao, Jin-Ming
Graphical abstract: Abstract: Eight isobutylhydroxyamides, including three new (1 –3 ), qinbunamides A–C, and five known sanshools (4 –8 ), ZP-amide A (4 ), ZP-amide B (5 ), ZP-amide E (6 ), ZP-amide C (7 ), and ZP-amide D (8 ), were isolated from the pericarps of cultivated Zanthoxylum bungeanum Maxim, cultivated in Qinling mountain area, Shaanxi, China. The structures of all compounds were determined on the basis of spectroscopic techniques, including 1D and 2D NMR analysis and comparison with previously reported data. Compounds1 and2 are the first example of isobutylhydroxyamides containing an ethoxy group, and compound3 is a rare C11 fatty acid-containing sanshool existing in genus Zanthoxylum . The tested compounds enhanced nerve growth factor (NGF)-mediated neurite outgrowth (neurotrophic activity) in rat pheochromocytoma (PC12) cells, but were inactive in the inhibitory effects on the 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical and growth of HCT116 cells at concentrations of 50 μM.